BBC to the rescue! - Smith, Paul (Javnost (Ljubljana), 2007)
Britain is almost unique in giving its incumbent public service broadcaster, the BBC, a leading role in driving digital, thereby hoping to hasten digital take-up, and thus allowing analogue switch-off by 2012. This paper is divided into two parts. The first part investigates the recent historical past with respect to the making of policy, drawing on the analytical framework of policycycles. Why has the British government given the BBC a lead role in the move towards digital transmission, and how does this decision link and interconnect with other interweaving policy debates surrounding the BBC licence fee and Charter renewal? In a media environment, increasingly driven by commercial considerations, what are the key policy motivations for entrusting a publicly funded institution with a lead role in the digital era, and what have been the main challenges and policy dilemmas in doing this? Part two considers how the BBC has responded to government policy initiatives. What are the key building blocks of its digital strategy and just how comfortably do these sit with its public service remit? For digital means much more than just broadcasting, demanding responses to changes in the way that audiences are likely to interact with content in future. Yet, in positioning itself as a content provider, whose content will be available on demand on myriad future platforms, the Corporation is increasingly impinging on what commercial operators believe is their future route to profitability. In the light of this analysis, the paper concludes by assessing the compatibility of government policy and BBC strategy given their at times diverging aims and objectives, and what this means for the continuance of a public service ethos into the digital age.
Keywords: management; Velika Britanija; množične komunikacije; digitalne komunikacije; digital television; digitalna televizija; plačevanje; dostopnost; razvojna strategija